Implications of opposite phyllotaxis for light interception efficiency of Mediterranean woody plants - Brites, Daniela; Valladares, Fernando (Trees, 2005)
Opposite leaves lead to a greater leaf overlapping than leaves spirally arranged along a shoot, decreasing light interception efﬁciency (Ea, fraction of the light reaching the plant actually intercepted by the leaves) of the crown. However, Ea results from a whole suite of morphological traits. The interplay between phyllotaxis, crown architecture, leaf morphology and Ea was explored in 12 woody species from Mediterranean-type ecosystems, where the abundance of woody species with opposite phyllotaxis is unusually high. The three-dimensional model Y-plant was used to estimate Ea in unbranched, vertical shoots of each species encompassing the natural morphological variation found from moderate shade to open light environments. Ea exhibited signiﬁcant interspeciﬁc differences, ranging from 0.25 in Daphne gnidium to 0.75 in Cistus ladanifer, Olea europaea and Salvia ofﬁcinalis, decreasing with leaf inclination angle and leaf area ratio (LAR), and increasing with internode-to-leaf-length ratio and supporting biomass. Species with spiral vs. opposite phyllotaxis did not differ in their mean Ea. However, the former had higher Ea than the latter at short internode lengths. The natural range of variation in internode length had a larger effect on Ea than the natural range of leaf elevation angle. Principal component analysis segregated species with opposite phyllotaxis from those with spiral leaves because of their greater self-shading for high sun elevation angles (>45 ◦ ); they were in turn distributed in two groups, one with high Ea, large investment in supporting biomass and long internodes, and another with low Ea and large LAR. Species with spiral phyllotaxis all had intermediate or low Ea and steep leaf elevation angles. Species with opposite phyllotaxis can compensate their less efﬁcient leaf arrangement by decreasing leaf elevation angle and increasing internode length, but they may experience a real phylogenetic constraint for light interception when biomass allocation to supporting tissues (internodes and petioles) becomes very costly. This constraint could be involved in the shade intolerance of woody Mediterranean species exhibiting opposite phyllotaxis.
Keywords: 3-D model; Crown architecture; Light interception efficiency; Mediterranean woody plants; Phyllotactic patterns

Implications of opposite phyllotaxis for light interception efficiency of Mediterranean woody plants - Brites, Daniela; Valladares, Fernando (Trees, 2005)
Opposite leaves lead to a greater leaf overlapping than leaves spirally arranged along a shoot, decreasing light interception efﬁciency (Ea, fraction of the light reaching the plant actually intercepted by the leaves) of the crown. However, Ea results from a whole suite of morphological traits. The interplay between phyllotaxis, crown architecture, leaf morphology and Ea was explored in 12 woody species from Mediterranean-type ecosystems, where the abundance of woody species with opposite phyllotaxis is unusually high. The three-dimensional model Y-plant was used to estimate Ea in unbranched, vertical shoots of each species encompassing the natural morphological variation found from moderate shade to open light environments. Ea exhibited signiﬁcant interspeciﬁc differences, ranging from 0.25 in Daphne gnidium to 0.75 in Cistus ladanifer, Olea europaea and Salvia ofﬁcinalis, decreasing with leaf inclination angle and leaf area ratio (LAR), and increasing with internode-to-leaf-length ratio and supporting biomass. Species with spiral vs. opposite phyllotaxis did not differ in their mean Ea. However, the former had higher Ea than the latter at short internode lengths. The natural range of variation in internode length had a larger effect on Ea than the natural range of leaf elevation angle. Principal component analysis segregated species with opposite phyllotaxis from those with spiral leaves because of their greater self-shading for high sun elevation angles (>45 ◦ ); they were in turn distributed in two groups, one with high Ea, large investment in supporting biomass and long internodes, and another with low Ea and large LAR. Species with spiral phyllotaxis all had intermediate or low Ea and steep leaf elevation angles. Species with opposite phyllotaxis can compensate their less efﬁcient leaf arrangement by decreasing leaf elevation angle and increasing internode length, but they may experience a real phylogenetic constraint for light interception when biomass allocation to supporting tissues (internodes and petioles) becomes very costly. This constraint could be involved in the shade intolerance of woody Mediterranean species exhibiting opposite phyllotaxis.
Keywords: 3-D model; Crown architecture; Light interception efficiency; Mediterranean woody plants; Phyllotactic patterns